Inverse Connected and Disjoint Connected Domination Number of a Jump Graph - Jasmine.S.E, Annie; Ameenal Bibi, K. (International Journal of Engineering and Technology, 2018)
Let D be the minimum connected dominating set of a jump graph . If  of  contains a connected dominating set , then  is called the inverse connected dominating set of the jump graph . The minimum cardinality of an inverse connected dominating set is the inverse connected domination number of the jump graph, denoted by. The disjoint connected domination number, of the jump graph , is the minimum cardinality of the union of two disjoint connected dominating set of  . In this paper we have established bounds, exact values of and graph theoretic relations between the inverse connected domination number of the jump graph with other parameters of G.